Polystyrene/calcium phosphate nanocomposites: Contact angle studies based on water and methylene iodide (eXPRESS Polymer Letters)
Polystyrene (PS) based nanocomposites were prepared by melt mixing in a Brabender Plasticoder with calcium phosphate as the nanofiller. These nanocomposites showed improvement in almost all physical properties. Contact angle measurements of the composites with water and methylene iodide were carried out. Various contact angle parameters such as total solid surface free energy, work of adhesion, interfacial free energy and spreading coefficient were analysed. The interaction parameter between the polymer and the liquids has been calculated using the Girifalco-Good’s equation.